Insect Diversity of the Muni-Pomadze Ramsar Site: An Important Site for Biodiversity Conservation in Ghana. (20th February 2014) - Kyerematen, Rosina; Acquah-Lamptey, Daniel; Owusu, Erasmus Henaku; Anderson, Roger Sigismund; Ntiamoa-Baidu, Yaa
Abstract : An inventory of species diversity of insects of the Muni-Pomadze Ramsar site, with special reference to species of conservation concern, was carried out as part of an evaluation of changes in the ecological character of the site, twenty years after designation. Samples were taken from two protected areas within the Ramsar site, in the wet (July), dry (January), and intermediate (June) seasons. Community diversity was characterized in terms of number of species accumulated, species richness, Shannon-Weiner indices of diversity, Pielou's evenness, and Bray-Curtis similarity. A total of 134 families from 19 insect orders were recorded during the entire study period. Yenku Block A recorded the highest species richness (98) and the highest diversity index (14.97), corroborated by the highest Margalef index of 3.82 with a relatively even distribution of species (0.834) during the intermediate season, and recorded the lowest diversity (6.957) and species richness (41) during the dry season. On the whole, the Muni-Pomadzi Ramsar site showed a high diversity of insect species. The presence of species such as Junonia oenone and Papilio demodocus which are specialized in degraded habitats at Yenku Block A in large numbers is a clear indication of degradation of the forest, but the presence of forest species such as Salamis anacardii and Euphaedra crokeri is an indication that some parts of this reserve are still in good shape. A comparison of the butterfly species recorded with findings in a 1997 survey showed a marked increase in numbers from 75 to 130; this may be attributed to the habitat changes that have taken place at the site offering more diverse habitat types.